You can put this solution on YOUR website!
The way you have written the equation the exponentiation (squaring) of (x+3) would not affect the constant multiplier 3. So, my assumption is that the equation is:
Divide both sides by 3.
(x+3)^2 = 54/3
(x+3)^2 = 18
x+3 = sqrt(18)
x = sqrt(18) -3
x = 3*sqrt(2) -3
Or we could expand the square and use factoring or quadratic equation for the solution.
(x+3)^2 = 54
x^2 +6x +9 = 54
x^2 +6x -45 = 0
|Solved by pluggable solver: SOLVE quadratic equation with variable|
|Quadratic equation (in our case ) has the following solutons:|
For these solutions to exist, the discriminant should not be a negative number.
First, we need to compute the discriminant : .
Discriminant d=216 is greater than zero. That means that there are two solutions: .
Quadratic expression can be factored:
Again, the answer is: 4.34846922834953, -10.3484692283495.
Here's your graph: